Parental Motivation and the Use of Technology in Children’s English Language Learning - Saputra, Eko Restu; Suryati, Nunung; Francisca Maria Ivone (Language Circle: Journal of Language and Literature, 2025)
Parents’ involvement in children’s English learning is vital. Moreover, nowadays, the ubiquity of technology-integrated learning materials is unavoidable. In the absence of updated research on the topic, the present descriptive qualitative study aims to scrutinize parents’ motivation and practices in helping their children’s English learning by using technology. The participants of this study were four parents. The data obtained from the semi-structured interview were analyzed by employing the interactive model of qualitative data analysis: data condensation, data display, and drawing conclusions and verifying. The result showed that the participants were driven to participate in their children's English learning process because they believed that English would benefit their children’s future existence while also allowing them to interact with society. Thus, it is important to escalate their English ability. It was undergone by providing their children with adequate English exposure, such as through daily interactions in English, English books, and even using technology with a screen-time agreement. Despite facing difficulty in utilizing technology, they managed it by establishing materials selection criteria, setting a screen-time limit, preparing back-up offline materials, also monitoring their children’ learning progress and outcome. The parents utilized technology by providing their children with relevant educational contents and platforms, which can be accessed by gadget. The findings of this study serve as references for parents to help their children learn English. Ultimately, future research is recommended to include a significant number of parents as participants in the study to gain deeper and more comprehensive findings.